Male-female differences in forearm skin tissue dielectric constant - Mayrovitz, Harvey N.; Carson, Sophia; Luis, Michelle (Clinical physiology and functional imaging, 2010)
Summary Tissue dielectric constant (TDC) measurements at 300 MHz via the coaxial line reflection method are useful to evaluate local skin tissue water and its change, but virtually all available data relate to measurements on women. Because TDC values in part depend on skin thickness, we hypothesized that differences in male–female skin may be associated with male–female differences in TDC. To test this hypothesis, we compared TDC values in volar forearm skin of 60 young adult volunteers (30 men, 25·0 ± 2·5 years, 30 women, 27·4 ± 6·6 years) in the seated position using a probe with an effective measurement depth of 1·5 mm. Results showed that TDC values (mean ± SD) for men were significantly greater than for women (33·2 ± 4·0 versus 29·4 ± 2·7, P<0·001) constituting an overall difference of about 13%. This finding suggests that when TDC measurements are used in research or clinical studies in which both men and women are included in a common study population, it would be prudent to consider this difference in both experimental design and data interpretation. This is especially true if absolute TDC values are of interest in contrast to changes in TDC values on the same subject subsequent to time passage or secondary to an intervention. Despite greater TDC values measured in men, calculations of the impact of a greater male skin thickness indicate that the greater TDC values of men may or may not reflect a greater relative local skin tissue water in men compared to women.